Digital Awareness Training and Education In SMA Negeri 6 Pekanbaru: Pelatihan dan Edukasi Kesadaran Digital Pada SMA Negeri 6 Pekanbaru - Yuhelmi, Yuhelmi; Devega, Mariza; Rebecca, Rebecca La Volla Nyoto (Institut Riset dan Publikasi Indonesia, 2025)
The “Digital Awareness Training and Education Program at SMA Negeri 6 Pekanbaru” aims to increase students' understanding in managing the use of technology wisely to maintain digital well-being. Problems faced by students include excessive use of technology, lack of self-management skills in the digital world, and the negative impact of social media on mental health. This training includes providing material on digital well-being, practice using Digital Wellbeing features, and evaluating the effectiveness of the program. The evaluation results showed a 51% increase in student understanding, especially in recognizing the negative impact of excessive technology use and how to set digital boundaries. The program helped students understand the balance between the digital world and real life and build healthier technology use habits. In the future, it is recommended that this training be conducted periodically with the involvement of parents as well as continuous evaluation to adjust to the ever-changing technological developments